2000
DOI: 10.1016/s1465-9972(00)00003-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen fertilization on atmospheric methane oxidation in boreal forest soils

Abstract: Importance of this Paper: The``greenhouse'' gas CH 4 is increasing in atmospheric concentration. Oxidation by methanotrophic bacteria in upland soils is the only biological sink for atmospheric CH 4 . Methanotrophs are inhibited by high soil N, raising concern that the contemporary worldwide increase in atmospheric N deposition will decrease soil CH 4 oxidation. The boreal forest occupies 13% of the earth's continental surface and is important in atmospheric CH 4 oxidation. We studied atmospheric CH 4 oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
6
11
0
2
Order By: Relevance
“…Although it is well documented that CH 4 uptake can be depressed by increased availability of inorganic N, our results are supported by several other field studies demonstrating no response in CH 4 uptake to N applications at similar or even higher application rates (e.g. Whalen and Reeburgh 2000). As for N 2 O responses it can also be argued that the lack of response to N application is related to the N delivery method, i.e.…”
Section: Impact Of Increased N Depositionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although it is well documented that CH 4 uptake can be depressed by increased availability of inorganic N, our results are supported by several other field studies demonstrating no response in CH 4 uptake to N applications at similar or even higher application rates (e.g. Whalen and Reeburgh 2000). As for N 2 O responses it can also be argued that the lack of response to N application is related to the N delivery method, i.e.…”
Section: Impact Of Increased N Depositionsupporting
confidence: 86%
“…There is evidence that the sink strength of CH 4 can be suppressed by additions of nitrogen Adamsen and King 1993;Wang and Ineson 2003;Bodelier and Laanbroek 2004). However, several other studies in forest systems found little or no response of CH 4 oxidation to N additions (Whalen and Reeburgh 2000;Bradford et al 2001;Steinkamp et al 2001). Increased atmospheric N-inputs have also been demonstrated to reduce soil CH 4 oxidation (Butterbach-Bahl et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The authors assumed that CH 4 oxidising bacteria may benefit from low N inputs, overcoming N limitation of bacterial growth. In contrast, repeated high inputs of a total of 140 and 530 kg N-NO 3 -ha −1 showed no effect on CH 4 uptake of a boreal spruce forest soil under field conditions (Whalen and Reeburgh 2000). Other field and laboratory approaches support our finding of reduced CH 4 uptake as a response to NO 3 − addition (Butterbach-Bahl et al 1998;Reay and Nedwell 2004;Ishizuka et al 2009).…”
Section: Discussionsupporting
confidence: 67%
“…Many authors have reported that N fertilization affects CH 4 oxidation in upland soils (Steudler et al 1989;King and Schnell 1994;Sitaula et al 1995;Gulledge et al 1997;Whalen and Reeburgh 2000). The inhibitory mechanism of CH.j oxidation in soils by N fertilization has been attributed to the factor that in soil both NH.j + oxidizers (nitrifiers) and CH 4 oxidizers (methanotrophs) are responsible for CH 4 oxidation.…”
Section: Soil Moisture and Ch 4 Fluxesmentioning
confidence: 99%